Towards practical lithium-metal anodes - Zhang, Xin; Yang, Yongan; Zhou, Zhen (Chemical Society reviews, 2020)
Lithium-ion batteries have had a tremendous impact on several sectors of our society; however, the intrinsic limitations of Li-ion chemistry limits their ability to meet the increasing demands of developing more advanced portable electronics, electric vehicles, and grid-scale energy storage systems. Therefore, battery chemistries beyond Li ions are being intensively investigated and need urgent breakthroughs toward commercial applications, wherein the use of metallic Li is one of the most intuitive choices. Despite several decades of oblivion due to safety concerns regarding the growth of Li dendrites, Li-metal anodes are now poised to be revived because of the advances in investigative tools and globally invested efforts. In this review, we first summarize the existing issues with regard to Li anodes and their underlying reasons and then highlight the recent progress made in the development of high-performance Li anodes. Finally, we propose the persisting challenges and opportunities toward the exploration of practical Li-metal anodes. Lithium ion batteries cannot meet the ever increasing demands of human society. Thus batteries with Li-metal anodes are eyed to revive. Here we summarize the recent progress in developing practical Li-metal anodes for various Li-based batteries.